A fault detection strategy using the enhancement ensemble empirical mode decomposition and random decrement technique. (August 2017) - Xiang, Jiawei; Zhong, Yongteng
Abstract: The vibration signals of mechanical components with faults are non-stationary and the feature frequencies of faulty bearings and gears are difficult to be extracted. This paper presents a new approach that combines the fast ensemble empirical mode decomposition (EEMD) to decompose the non-stationary signal into stationary components, the random decrement technique (RDT) to extract the impulse signals of stationary components, and Hilbert envelope spectrum to demodulate the impulse signals to detect faults in bearings and gears. The proposed approach uses the fast EEMD algorithm to extract intrinsic mode functions (IMFs) from vibration signals able to tack the feature frequency of bearings and gears. IMF1 is further extracted by the RDT, and the feature frequencies are determined by analysing the signals using Hilbert envelope spectrum. Numerical simulations and experimental data collected from faulty bearings and gears are used to validate the proposed approach. The results show that the use of the EEMD, the RDT, and the Hilbert envelope spectrum is a suitable strategy to detect faults of mechanical components. Highlights: A RDT based EEMD approach is proposed to detect faults. EEMD and RDT are employed to decompose signals, extract the impulse signals, respectively. It is a suitable strategy to detect faults of mechanical components.